2022
DOI: 10.3390/nano12101767
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis and Optimization of a PBDB-T:ITIC Based Organic Solar Cell Using Graphene Oxide as the Hole Transport Layer

Abstract: The hole transport layer (HTL) in organic solar cells (OSCs) plays an imperative role in boosting the cell’s performance. PEDOT: PSS is a conventional HTL used in OSCs owing to its high design cost and instability issues. It can be replaced with graphene oxide to increase the cell performance by overcoming instability issues. Graphene oxide (GO) has gained popularity in recent years for its practical use in solar energy due to its remarkable mechanical, electrical, thermal, and optical properties. This work us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Some promising materials based on Eu and Dy were used by several groups. They provided the possibility of efficiency improvement in various cells' structures and configurations, most prominently for quantum dot-sensitized solar cells (QDSSCs) [74,75]. These materials even became commercially available in the form of luminescent powders such as Sr 4 Al 14 O 25 : Eu, Dy (BGL-300M), and SrAl 2 O 4 : Eu, and Dy (G-300M) by NEMOTO LUMIN-NOVA ® [76].…”
Section: Rare Earth Elements and Other Inorganic Materials For Lumine...mentioning
confidence: 99%
“…Some promising materials based on Eu and Dy were used by several groups. They provided the possibility of efficiency improvement in various cells' structures and configurations, most prominently for quantum dot-sensitized solar cells (QDSSCs) [74,75]. These materials even became commercially available in the form of luminescent powders such as Sr 4 Al 14 O 25 : Eu, Dy (BGL-300M), and SrAl 2 O 4 : Eu, and Dy (G-300M) by NEMOTO LUMIN-NOVA ® [76].…”
Section: Rare Earth Elements and Other Inorganic Materials For Lumine...mentioning
confidence: 99%
“…In [ 34 ], the PTB7:PC 70 BM blend has been explored with different electron transport layer (ETL) materials, and it was found that Zn(O,S) is the most suitable partner, that achieved a PCE of 17.15%. Some simulation studies inspected the replacement of the conventional PEDOT:PSS with other promising candidates [ 35 , 36 , 37 ]. Regarding these simulation studies, and many others, all-polymer SCs based on polymerized acceptors have not been investigated by simulation until now, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene can be conducted as a kind of functional material for flexible and transparent devices due to its unique structures, excellent physical properties, and terrific mechanical and flexible characteristics, which result in lots of potential applications in the fields of biosensors [ 1 , 2 ], supercapacitors [ 3 ], liquid crystal devices [ 4 ], electronic devices [ 5 ], solar cell [ 6 , 7 ], catalysts [ 8 ], and even in energy storage and battery applications [ 9 ]. Owing to the sp 2 bonds and π bond with carbon atoms tightly and regularly arranged in a single layer of hexagonal honeycomb-like, two-dimensional structures [ 10 ], the electrons in graphene can move freely which result in an excellent electrical conductivity and very high mobility at room temperature [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%